The role of OsPT8 in arsenate uptake and varietal difference in arsenate tolerance in rice - Wang, Peitong; Zhang, Wenwen; Mao, Chuanzao; Xu, Guohua; Zhao, Fang-Jie (Journal of experimental botany, 2016)
Arsenic (As) contamination in paddy soil can cause phytotoxicity and elevated As accumulation in rice grain. Rice varieties vary in As uptake and tolerance, but the underlying mechanisms remain unclear. In this study, the aus variety Kasalath was found to be more tolerant to arsenate [As(V)] than the japonica variety Nipponbare, but the two varieties showed similar arsenite [As(III)] tolerance. Nipponbare took up more phosphate (Pi) and As(V) than Kasalath. The expression of genes for Pi transporters or Pi homeostasis regulation was quantified. Nipponbare showed 2- to 3-fold higher expression of the Pi transporter genes OsPT2 and OsPT8 than Kasalath. Two ospt8 mutants were isolated from the Kasalath background and compared with an ospt8 mutant in the Nipponbare background. Mutation in OsPT8 in both backgrounds decreased As(V) uptake by 33–57%, increased As(V) tolerance assayed by root elongation by >100-fold, and abolished the varietal differences in As(V) uptake and tolerance. The results show that OsPT8 plays a key role in As(V) uptake and that As(V) uptake mediated by OsPT8 exerts a profound toxic effect on root elongation. The results also suggest that differential OsPT8 expression explains the varietal differences in As(V) uptake and tolerance between Kasalath and Nipponbare.